Prolonged Standing Task Affects Adaptability of Postural Control in People With Parkinson’s Disease - Moretto, Gabriel Felipe [UNESP]; Santinelli, Felipe Balistieri [UNESP]; Penedo, Tiago [UNESP]; Mochizuki, Luis; Rinaldi, Natalia Madalena; Barbieri, Fabio Augusto [UNESP] (SAGE Publications, 2021)
Background: Studies on short-term upright quiet standing tasks have presented contradictory findings about postural control in people with Parkinson’s disease (pwPD). Prolonged trial durations might better depict body sway and discriminate pwPD and controls. Objective: The aim of this study was to investigate postural control in pwPD during a prolonged standing task. Methods: A total of 26 pwPD and 25 neurologically healthy individuals performed 3 quiet standing trials (60 s) before completing a constrained prolonged standing task for 15 minutes. Motion capture was used to record body sway (Vicon, 100 Hz). To investigate the body sway behavior during the 15 minutes of standing, the analysis was divided into three 5-minute-long phases: early, middle, and late. The following body sway parameters were calculated for the anterior-posterior (AP) and medial-lateral (ML) directions: velocity, root-mean-square, and detrended fluctuations analysis (DFA). The body sway area was also calculated. Two-way ANOVAs (group and phases) and 1-way ANOVA (group) were used to compare these parameters for the prolonged standing and quiet standing, respectively. Results: pwPD presented smaller sway area (P <.001), less complexity (DFA; AP: P <.009; ML: P <.01), and faster velocity (AP: P <.002; ML: P <.001) of body sway compared with the control group during the prolonged standing task. Although the groups swayed similarly (no difference for sway area) during quiet standing, they presented differences in sway area during the prolonged standing task (P <.001). Conclusions: Prolonged standing task reduced adaptability of the postural control system in pwPD. In addition, the prolonged standing task may better analyze the adaptability of the postural control system in pwPD.
Keywords: human movement; Parkinson’s disease; postural control; prolonged standing